Diversity of Axonal and Dendritic Contributions to Neuronal Output - Goaillard, Jean-Marc; Moubarak, Estelle; Tapia, Mónica; Tell, Fabien (Frontiers in Cellular Neuroscience, 2020)
Our general understanding of neuronal function is that dendrites receive information that is transmitted to the axon, where action potentials are initiated and propagated to eventually trigger neurotransmitter release at synaptic terminals. Even though this canonical division of labor is true for a number of neuronal types in the mammalian brain (including neocortical and hippocampal pyramidal neurons or cerebellar Purkinje neurons), many neuronal types do not comply with this classical polarity scheme. In fact dendrites can be the site of action potential initiation and propagation, and even neurotransmitter release. In several interneuron types, all functions are carried out by dendrites as these neurons are devoid of a canonical axon. In this article, we present a few examples of "misbehaving" neurons (with a non-canonical polarity scheme) to highlight the diversity of solutions that are used by mammalian neurons to transmit information. Moreover, we discuss how the contribution of dendrites and axons to neuronal excitability may impose constraints on the morphology of these compartments in specific functional contexts.